Sequential evaluation of crestal bone levels around implant restored with platform switching in mandibular molars using CBCT: An In vivo study - Sumit Jairao Deshpande; Syed Abdul Qayum; Girish Katti; Gopala Abhishek; Aishwarya Raju; Chandrika Katti (Wolters Kluwer Medknow Publications, 2023)
Background: The single most crucial aspect in deciding whether a dental implant will be effective is the existence of healthy crestal bone. Objective: To measure and evaluate the crestal bone levels around dental implants placed using single-stage implant surgery at mandibular 1st molar region with platform-switched healing abutment and restored platform-switched prosthesis by using CBCT at different time intervals in a period of 12 months. Method: Fifteen patients were selected from the outpatient department of prosthodontics. CBCT was made preoperative, and postoperative, immediately after the platform-switched prosthesis fit-in, after 3 and 6 months of prosthesis fit-in to evaluate the vertical crestal bone level changes using CBCT. Results: In the present study radiographic evaluation of crestal bone demonstrated mean changes of 0.94667 mm in 3rd month, and 0.41500 mm at 6th month follow-up. At the 12th month, post-operatively crestal bone level changes were 0.58167 mm with single-stage surgery loaded with platform-switched abutment, which shows significantly favorable: bone level changes. Conclusion: The data analysis revealed that crestal bone levels around dental implants were preserved and regenerated as a result of stress concentration shifting away from the crestal areas which ultimately contributes to the long-term success of dental implants.